The efforts to improve mathematics learning in material three-dimensional shapes by use of concrete learning objects - Junitawati, Junitawati; Abidin, Achmad Anwar (Nashir Al-Kutub Indonesia, 2024)
This research was motivated by the low learning outcomes of mathematics and the low ability of teachers to use the right learning model in mathematics lessons three-dimensional shapes material in students. The purpose of learning improvement research is to improve student learning outcomes in mathematics lessons about the material three-dimensional shapes Space by using concrete learning object. This study used the Kemmis and McTaggart model classroom action research procedure for two cycles with stages, including: planning, action, observation, and reflection. The results showed that the use of concrete media in the material of recognizing building simple space was proven to improve the learning outcomes of students in mathematics lessons of the material three-dimensional shapes. This can be seen from the activeness of students in learning and increasing student learning outcomes. Thus, it can be concluded that the use of concrete learning object can improve the learning outcomes of mathematics material to recognize building simple spaces in students.